Finding Its Place: The Effect of Race on Drug Court Outcomes - (:unkn) unknown (My University, 2013)
The most recent statistics on United States adult drug courts indicate that there are more than 1,400 courts currently in operation nationwide (National Institute of Justice 2013). This number is rather astounding, given that drug courts only emerged in Miami, Florida in 1989. However, what is more astounding is the fact that in the two decades drug courts have existed, they have been studied more than all other criminal justice programs combined (Honda and Sheen 2011; Marlowe 2010). As successfully completing one's drug court program (i.e., graduating) often indicates whether a former participant will recidivate, myriad researchers and federally-funded studies have used graduation rates to measure the effectiveness of drug courts. However, inconsistencies remain in drug court literature, particularly that of whether the race of program participants affects graduation. This is in part due to the failure of previous studies to control for a number of legal, extralegal, and programmatic variables that have been found to influence drug court outcomes, as well as problems with small sample sizes and single-site studies. Therefore, this study further investigates drug court graduation rates and asks to what extent can drug court outcomes be assigned solely to the basis of race?
Keywords: Drug Court; Graduation; Race